Postsurgery paths and outcomes for hip fracture patients (POST-OP HIP PATHS): a population-based retrospective cohort study protocol - Chantal Backman; Peter Tanuseputro; Colleen Webber; Paul Beaule; Stephane Poitras; Steve Papp; Anne Harley; Soha Shah; Randa Berdusco; Véronique French-Merkley; Luke Turcotte; D I McIsaac (BMJ Open)
Introduction Hip fracture patients receive varying levels of support posthip fracture surgery and often experience significant disability and increased risk of mortality. Best practice guidelines recommend that all hip fracture patients receive active rehabilitation following their acute care stay, with rehabilitation beginning no later than 6 days following surgery. Nevertheless, patients frequently experience gaps in care including delays and variation in rehabilitation services they receive. We aim to understand the factors that drive these practice variations for older adults following hip fracture surgery, and their impact on patient outcomes.Methods and analysis We will conduct a retrospective population-based cohort study using routinely collected health administrative data housed at ICES. The study population will include all individuals with a unilateral hip fracture aged 50 and older who underwent surgical repair in Ontario, Canada between 1 January 2015 and 31 December 2018. We will use unadjusted and multilevel, multivariable adjusted regression models to identify predictors of rehabilitation setting, time to rehabilitation and length of rehabilitation, with predictors prespecified including patient sociodemographics, baseline health and characteristics of the acute (surgical) episode. We will examine outcomes after rehabilitation, including place of care/residence at 6 and 12 months postrehabilitation, as well as other short-term and long-term outcomes.Ethics and dissemination The use of the data in this project is authorised under section 45 of Ontario’s Personal Health Information Protection Act and does not require review by a Research Ethics Board. Results will be disseminated through conference presentations and in peer-reviewed journals.